THE ROLE OF FUN AND GAMES IN THE LESSONS - Saidova Kamola Ilkhomjonovna (Research Focus International Scientific Journal, 2025)
Research has shown that games are essential for healthy development in early childhood and beyond. Play lets children practise what they know and also what they don't. It allows them to experiment through trial and error, find solutions to problems, work out the best strategies, and build new confidence and skills.